ANALISIS TATA RUANG DALAM KENYAMANAN KERJA DAN OPTIMALISASI KINERJA BAGIAN HUMAS DAN PROTOKOL SEKRETARIAT DPRD KOTA SURAKARTA - Firda Noor Oktavianti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2018)
This research aims to determine: (1) Office layout that has been established in spatial planning Sub Division of Public Relations and Protocol. (2) Obstacles and efforts to achieve employee convenience in Sub Division of Public Relations and Protocol. (3) The office layout design which effective to optimize the employee performance at Sub Division of Public Relation and Protocol. This research is a descriptive qualitative research. The subject taking technique used purposive sampling and snow ball sampling. The validity of data were triangulation of source data and triangulation of method. Data analysis technique used interactive analysis model. This Research shows that (1) Office layout in Sub-Division of Public Relations and Protocol Secretariat DPRD of Surakarta has not fully apply the principles of office layout. (2) The factors to derive the employee’s work convenience consists of light, air conditioner and ventilation, paint color of the wall are enough to encourage staff more comfortable in doing their work. (2) The effective office layout for the Sub-Division of Public Relations and Protocol is an open office layout with the placement of computer placed in accordance with the needs of staff who often use it.